Aetiopathogenesis of Vitiligo - Katia Boniface (Mattioli1885, 2023)
Vitiligo is a chronic auto-immune disease characterized by skin depigmentation due to the loss of melanocytes. The better understanding of the disease mechanisms is currently undergoing a significant dynamism, opening a new era in therapeutic development. The pathophysiology of vitiligo has attracted the attention of researchers for years and many advances have been made in clarifying the crosstalk between the cellular players involved in the development of vitiligo lesions. The understanding of the complex interactions between epidermal cells (i.e.  melanocytes and keratinocytes), dermal fibroblasts, and immune cells, led to a better characterization of the signals leading to the loss of melanocytes. Recent advances highlighted the role resident T memory cells in the development and recurrence of lesions. This narrative review aims to give an overview of the mechanisms leading to melanocyte disappearance in vitiligo, with a focus on the intercellular interaction network involved in the activation of the local skin immune response.